Mysticism and philosophy in al-Andalus : Ibn Masarra, Ibn al-'Arabi and the Isma'ili tradition - Ebstein, Michael. (Islamic History and Civilization, 2014)
Muslim Spain gave rise to two unusual figures in the mystical tradition of Islam: Ibn Masarra (269/883-319/931) and Ibn al-ʿArabī (560/1165-638/1240). Representing, respectively, the beginning and the pinnacle of Islamic mysticism in al-Andalus, Ibn Masarra and Ibn al-ʿArabī embody in their writings a type of mystical discourse which is quite different from the Sufi discourse that evolved in the Islamic east during the 9th-12th centuries. In Mysticism and Philosophy in al-Andalus , Michael Ebstein points to the Ismāʿīlī tradition as one possible source which helped shape the distinct intellectual world from which both Ibn Masarra and Ibn al-ʿArabī derived. By analyzing their writings and the works of various Ismāʿīlī authors, Michael Ebstein unearths the many links that connect the thought of Ibn Masarra and Ibn al-ʿArabī to the Ismāʿīlī tradition.